Khadijah bint Khuwaylid: Sacrifice in the Religion of Islam - Nafila, Linta Rahma; Na'im, Muhammad Ainun; Budianto, Bunga Firdausya; Huda, Muhammad Miftahul (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study explores the story of Khadijah bint Khuwaylid and her sacrifices in the spread of Islam, as narrated in Hadith and indirectly referenced in the Qur’an. It serves as both a historical and theological reflection on the rise of Islamic teachings. Khadijah, the first wife of the Prophet Muhammad, holds a prominent place in Islamic history. However, the depth and scope of her sacrifices, and their specific contributions to the spread of Islam, warrant deeper examination. This paper aims to analyze the impact of Khadijah bint Khuwaylid’s sacrifices on the development of Islam during the early period of prophethood. The study employs a library research method, drawing on various credible sources.The findings are expected to reveal that Khadijah’s unwavering financial, moral, and emotional support for the Prophet Muhammad played a crucial role in the early propagation of Islam. Her support helped strengthen the Prophet’s position, overcome the challenges of da'wah, and lay a solid foundation for the first Muslim community.The study adopts a qualitative descriptive method using thematic exegesis and historical analysis. The primary sources are the Qur’an and Hadith, particularly verses that relate indirectly to the story of Khadijah—such as those found in Surah Al-Ahzab and Surah Al-Hajj—supported by classical and contemporary exegesis and Hadith literature.This research is expected not only to provide a more comprehensive understanding of the magnitude of Khadijah bint Khuwaylid’s sacrifices in supporting the early Islamic mission, but also to inspire today’s Muslim generations to emulate her steadfast faith, selfless sacrifice, and sincere moral support in upholding Islamic values. The findings are hoped to enrich Islamic scholarship, particularly in recognizing the vital role of women in the historical development of the religion.